2012
DOI: 10.5620/eht.2012.27.e2012016
|View full text |Cite
|
Sign up to set email alerts
|

The Margin of Exposure of 5-Hydroxymethylfurfural (HMF) in Alcoholic Beverages

Abstract: Objectives5-Hydroxymethylfurfural (HMF) regularly occurs in foods and in alcoholic beverages. However, the risk of HMF associated with alcohol consumption has not been systematically studied, so that this study will provide the first quantitative risk assessment of HMF for consumers of alcoholic beverages.MethodsHuman dietary intake of HMF via alcoholic beverages in the European Union was estimated based on WHO alcohol consumption data combined with our own survey data (n=944) and literature data (n=147) about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…These results confirmed the central role of oil concentration in roasted hazelnuts, as the HMF content increased from 66.5 to 144.0 mg/kg in non-defatted specimens exposed to extended dry heating (from 30 to 60 min, respectively) [39]. Monakhova and Lachenmeier [40] reported that HMF can be formed in most heat-treated foods with a variation in the levels ranged from trace concentration in juices to nearly 4,000 mg/kg in coffee.…”
Section: Occurrence and Dietary Exposure To Hmfsupporting
confidence: 68%
“…These results confirmed the central role of oil concentration in roasted hazelnuts, as the HMF content increased from 66.5 to 144.0 mg/kg in non-defatted specimens exposed to extended dry heating (from 30 to 60 min, respectively) [39]. Monakhova and Lachenmeier [40] reported that HMF can be formed in most heat-treated foods with a variation in the levels ranged from trace concentration in juices to nearly 4,000 mg/kg in coffee.…”
Section: Occurrence and Dietary Exposure To Hmfsupporting
confidence: 68%
“…methanol, HMF, and higher alcohols) were within normal ranges for this product category and below toxicological thresholds (for limits including toxicological assessment see Lachenmeier et al (2011b and Monakhova and Lachenmeier (2012)). …”
Section: Resultsmentioning
confidence: 99%
“…37 The TAMDI assumes that the consumer will day in day out take a fixed standard amount of flavoured food and beverages which will always contain the specific flavouring at its specified upper use level. On the other hand, the maximum EDI values (26.71-86.71 μg kg bw −1 day −1 ) of HMF found in carob liquors were well below the benchmark dose lower confidence limit (BMDL) (79 mg kg bw −1 day −1 ) (dose that corresponds to a specific change in an adverse response compared to the response in unexposed subjects), 38 the range of average daily intake of 30-150 mg person −1 established by Janzowski et al, 39 and the threshold of concern (540 μg person −1 day −1 ) and the modified theoretical added maximum daily intake (mTAMDI, 1600 μg person −1 day −1 ) established by the European Food Safety Authority. 37…”
Section: Quantification Of Furfural and 5-(hydroxymethyl)furfural Esmentioning
confidence: 84%